"Entlassungsurkunde aus dem preussischen Unterthanenverbande". Trier. Original in Marx/Engels archive, E 18
"Entlassungsurkunde aus dem preussischen Unterthanenverbande". Trier. Original in Marx/Engels archive, E 18.